MENGGALI POTENSI JIWA KEWIRAUSAHAAN MAHASISWA PTAIN DI SUMATERA BARAT - Harfandi, Harfandi (jurnal ekonomi, 2014)
The etrepreneurship potential of student?sThe Islamic State College ?PTAIN- in West Sumatera has showed that the student?s entrepreneurship potential was on medium category but was inclined tobe hight. Some absolute the character of entrepeneurship which is strong (based on student?s perception) are working hard character, good appearance, faith, capable on making decision, willing to improve knowledge, progress ambition, communicative have job commitment, responsible, entrepreneurship interest, chance to reach future obsession, energetic, motivation to be superior, have orientation to the future, willing to learn from the failure. But same character which is not strong are team work ability with other, want to receive soon, creative, flexible, leading ability, and tolerance.